Benefits of switching women schizophrenic patients to aripiprazole: a case study and brief review of the literature - Kuloglu, Murat; Ekinci, Okan; Albayrak, Yakup; Caykoylu, Ali (Springer Wien, 2010)
Hyperprolactinemia, an adverse side-effect of the use of typical and some atypical antipsychotics, has both acute and chronic clinical consequences. When observed in schizophrenic patients, it may be treated by switching the patient to an antipsychotic agent with a lower liability for the induction of hyperprolactinemia. The effects of substituting aripiprazole for other antipsychotic agents on schizophrenic patients with antipsychotic-induced hyperprolactinemia have been previously reported in several studies. Many studies have also noted that aripiprazole can sometimes lead to increases in psychotic symptoms, especially in the period immediately following the switch or when aripiprazole is combined with a dopamine antagonist. Here, we report observations on five female patients who were experiencing symptomatic hyperprolactinemia and psychotic exacerbation while on antipsychotic treatment, yet improved in both conditions after being switched to aripiprazole monotherapy. We also provide a brief review of the existing studies that report the results of switching patients from other antipsychotics to aripiprazole.
Keywords: Aripiprazole; Hyperprolactinemia; Schizophrenia; Switching